Sentado en un carrusel: Fuga de capital en el Ecuador (2018-2020) - Meyer, Eric Stefano (2021)
The article studies the process of capital flight form a monetary point of view. We identify systemic conditions for the possibility of continuous flight that derive from the nature of international payments. The data for Ecuador for the years 2018-2020 allow us to identify a "merry-go-round" of public indebtedness and acquisition of external private assets, a process that we interpret - tentatively - as an expression of the contradictions of the peripheral accumulation process and its mediation by the nation-state.